(untitled) (Journal of Nobel Medical College, 2021)
Background: Thyroid hormones are necessary for the growth and development, cellular differentiation, physiological function and metabolic regulation of almost all tissues in our body. Thyroid disorders are accompanied by alteration in hematological profile. This study aims to evaluate the effect of thyroid dysfunction on red blood cell parameters. Materials and Methods: This case-control observational study was conducted in the Department of Clinical Biochemistry, KIST Medical College and Teaching Hospital (KISTMCTH), Lalitpur, Nepal from January 2021 to June 2021.Total number of recruited subjects was 248, out of which 67 were labeled as hypothyroid, 7 were hyperthyroid and 174 were euthyroid as control. Subjects for all three groups were between 16-93 years old. Thyroid hormone profile of patients was determined by Siemens ADVIA Centaur CP immunoassay analyzer and hematological parameters by automated hematology analyzer Sysmex XN-550. Results were analyzed by SPSS 21 software and a chi-square test was applied to see significant differences among the groups. Results: The mean age of all study participants was 42.08±17.27 years and female constituted 74.6% of total subjects. Analysis of the data obtained a statistically significant difference in the mean hemoglobin (p<0.001) between hypothyroid and euthyroid groups. The difference was not significant for hemoglobin (p=0.252) among hyperthyroid and euthyroid groups. There was no statistical significant difference between thyroid cases and control for MCV, MCH and MCHC. Conclusion: The current study concluded that thyroid dysfunction have a significant effect on red blood cell parameters. Hematological parameters should be evaluated in patient with thyroid dysfunction.